Women’s Authority in the Perspective of Hadith: A Thematic and Contextual Analysis - Chaerul Mundzir; Arifuddin Ahmad; Zulfahmi Alwi; Muhammad Irfan Hasanuddin (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2025)
The study of women’s authority from the perspective of ḥadīth is a timely issue in contemporary discourse, particularly regarding women’s roles in leadership and decision-making across various spheres. This research aims to explore the understanding of ḥadīths related to women’s authority, both in normative and historical contexts. The findings indicate that comprehension of ḥadīths concerning women’s authority requires a contextual approach that accounts for the social, cultural, and historical backgrounds in which these traditions emerged. Furthermore, this study emphasises the importance of distinguishing between universally normative ḥadīths and those that are locally contextual. In many cases, women’s authority is not inherently constrained by religious normative texts, but is instead shaped by scholarly interpretations influenced by patriarchal contexts. This article recommends a re-reading of ḥadīths using a critical hermeneutic approach to uncover more inclusive dimensions of gender justice. By doing so, the understanding of women’s authority in Islam can contribute to establishing a more equitable and just social order, without compromising the core values taught in the religion.